Plasmacytoma Masquerading as Meningioma - Erdem, Münibe Büşra; Çakmak, Pınar; Akyürek, Nalan; Dogulu, Fikret (Indian Journal of Neurosurgery, 2020)
Solitary bone plasmacytoma is a rare disease in the skull. We present a 70-year-old patient who presented with a skull deformity due to the left parietooccipital tumor. Neurological examination found no deficit. The systemic scanning revealed no additional lesion. The surgery was planned, and the tumor was removed totally with the marginal bone around it. Histopathological examination confirmed solitary bone plasmacytoma. The patient is being followed-up without recurrence or progression to multiple myeloma. As the calvarial solitary bone plasmacytomas can be easily misdiagnosed preoperatively, the detailed examination of the CT features may be helpful for the planning and course of the surgery.
Keywords: plasmacytoma; skull neoplasms; osteolysis